Aptamer-based thin film gold electrode modified with gold nanoparticles and carboxylated multi-walled carbon nanotubes for detecting oxytetracycline in chicken samples. (1st December 2019) - He, Baoshan; Wang, Long; Dong, Xiaoze; Yan, Xiaohai; Li, Ming; Yan, Sasa; Yan, Dandan
Highlights: Apt-TFGE offers portability and possibility for on-site analysis. Apt-TFGE shows a high sensitivity and wide linear range for OTC detection. The Apt-TFGE exhibits good reproducibility, selectivity and stability. The constructed Apt-TFGE is successfully applied to detect OTC in actual samples. Abstract: In this work, a disposable and portable aptasensor for the fast and sensitive detection of oxytetracycline (OTC) using gold nanoparticles (AuNPs)/carboxylated multi-walled carbon nanotubes (cMWCNTs)@thionine connecting complementary strand of aptamer (cDNA) as signal tags was constructed. The substrate electrode of the aptasensor was thin film gold electrode (TFGE), which have the advantages of portable and uniform performance. In the presence of OTC, OTC competed with cDNA to combine with aptamer. The bioconjugate (AuNPs/cMWCNTs/cDNA@thionine) was released from the TFGE. Thus, the electrochemical signal declined. Under optimized conditions, the aptasensor exhibited good stability, high selectivity and high sensitivity. Furthermore, the developed electrochemical aptamer-based TFGE had a wide dynamic range of 1 × 10 −13 –1 × 10 −5  g mL −1 for target OTC with a low detection limit of 3.1 × 10 −14  g mL −1 and was successfully used for the determination of OTC in chicken sample.